2021
DOI: 10.1080/13467581.2021.1903905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the 3D cooling performances of different vegetation combinations in the urban area

Abstract: Vegetation has been considered as an effective strategy to combat the urban heat island effect. Most researches have focused on evaluating the cooling effect of trees in the urban thermal environment. Little attention has been paid to the cooling effect of the combination of different vegetation elements. Moreover, most studies are focused on the horizontal cooling performance of plants, while fewer studies have investigated the vertical cooling effect of vegetation. Therefore, this study evaluates the 3D (hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…The surface energy balance and the hydrosphere-atmosphere water vapor cycle are both influenced by tree transpiration. It is also the primary cause of the ecological effects of trees, such as cooling and humidification [19]. As mentioned previously, the real temperature at noontime was measured at 52 ºC.…”
Section: Resultsmentioning
confidence: 99%
“…The surface energy balance and the hydrosphere-atmosphere water vapor cycle are both influenced by tree transpiration. It is also the primary cause of the ecological effects of trees, such as cooling and humidification [19]. As mentioned previously, the real temperature at noontime was measured at 52 ºC.…”
Section: Resultsmentioning
confidence: 99%
“…It means the higher the Tmrt value, the higher the PET value. According to Tan [15], the Tmrt value is influenced by how much shading is produced from the presence of vegetation or buildings around the measurement location. This shows that the presence of shadows greatly affects the thermal comfort value in the Green Park Kitakyushu.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, shadows can directly affect the 3D cooling effect of the vegetation combination. The larger the shaded area, the better the cooling effect for the same vegetation cover [15]. A study in Sao Paulo found that during autumn, April 2013, the average maximum air temperature difference reached 0.5 • C and in February 2014, during the extreme warm summer, air temperature differences became more significant, and the effect of vegetation was slightly more pronounced showing maximum air temperature differences up to 0.6 • C [14].…”
Section: Thermal Comfort Studiesmentioning
confidence: 99%
See 2 more Smart Citations